Developing a Learning Tools of Problerm Based Learning (PBL) Using Number Pockets Media To Improve The Student's Critical Thinking Ability in Social Science Subject Of 4th Grade Student of Elementary School - Kusumaningrum, Wahyu; Fakhruddin, Fakhruddin; Prihatin, Titi (Educational Management, 2021)
This study aims to (1) determine the validity of the learning tools of Problems Based Learning using the Number Pocket media in the 4th grade student of elementary school; (2) determine the students’ response to the development of the learning tools of Problem Based Learning using the Number Pocket media in the 4th grade student of elementary school; (3) determine the effect to students’ learning achievement; (4) determine the effect to students' critical thinking ability; (5) determine the quality of the learning tools of Problem Based Learning using the Numbers Pocket media in terms of validity, practicality and effectiveness aspects. The type of this study is research and development with 4-D model. The sampling technique used was purposive sampling, obtained by class IV-A of Pakunden Elementary School as a control group and class IV-B as an experiment group. The result of this study showed that (1) The validation result of the RPP, LKS and the Numbers Pocket media obtained an average score 4.36, 4.49, and 4.75 “very good classification”; (2) Students’ response questionnaire analysis obtained score 4.19